Alteration of Pressure-Induced Vasodilation in Aging and Diabetes, a Neuro-Vascular Damage - Fouchard, Maxime; Misery, Laurent; Le Garrec, Raphaële; Sigaudo-Roussel, Dominique; Fromy, Bérengère (Frontiers in Physiology, 2019)
Skin is constantly subjected to pressure at different levels. Pressure-induced vasodilation (PIV) is one of the response mechanisms to low pressure that maintains the homeostasis of the skin. PIV results from the interaction of primary afferent nerves and vascular endothelium of skin vessels. Thanks to this cutaneous neuro-vascular interaction, the cutaneous blood flow increase allows the maintenance of an optimal level of oxygenation and minimizes the lack of vascularization of the skin tissue under low pressure. It seems to be associated with the cutaneous protection mechanisms to prevent pressure ulcers. In some contexts, where microangiopathy and neuropathy can occur, such as ageing and diabetes, PIV is impaired, leading to a dramatic early decrease in local skin blood flow when low pressure is applied. In ageing, PIV alteration is due to endothelial dysfunction, essentially from an alteration of the nitric oxide pathway. In the inflamm-aging context, oxidative stress increases leading to endothelial cell and nerve damages. An age-related sensory neuropathy will exacerbate the alteration of PIV during the aging process. In diabetes, non-controlled hyperglycaemia leads to an increase in several pathological biochemical pathways that involve oxidative stress and can affect PIV. Sorbinil, alagebrium and alpha-lipoic acid are able individually to restore PIV through a possible oxidative stress reduction. Candesartan, an angiotensin II type 1 receptor blocker, is also able to restore PIV and prevent pressure ulcer formation. The possibility of preventing pressure ulcer associated to diabetes and/or ageing with the restoration of PIV seems to be a promising research path.